Effect of different seat support characteristics on the neck and trunk muscles and forward head posture of visual display terminal workers. - Yoo W; Kim M (Work, 2010)
Objective: This study was designed to identify the effect of seat support characteristics on the neck and trunk muscles and forward head posture of visual display terminal (VDT) workers working at computers. Participants: 22 VDT workers with forward head posture were asked to perform computer work. Methods: Surface electromyography recorded the five neck and trunk muscles Forward head angle was analyzed with a 3-D motion analysis system. The significance of differences in the seat supports (hard, spongy, unstable) was tested by repeated one-way ANOVA with the significance cutoff set at [alpha] = 0.05. Results: Computer work seated on an unstable cushion-ball as compared to a spongy soft-cushion seat support showed significantly lower midcervical and L5 paraspinal muscle activity and significantly higher lower trapezius and internal oblique abdominal muscle activity. The mean forward head angle decreased in the order of spongy, hard, and unstable seat supports. Conclusions: An unstable cushion-ball seat support may prevent work-related neck and upper limb disorders associated with forward head posture.